2019
DOI: 10.15666/aeer/1701_085105
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis on Responses of Vegetation Productivity Relative to Different Drought Monitor Patterns in Karst Regions of Southwestern China

Abstract: Zhou et al.: Comparative analysis on responses of vegetation productivity relative to different drought monitor patterns in karst regions of Southwestern China -85 -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…We used a total of seven predictor variables (Table 1) in order to explain the vegetation productivity. These variables were selected since they are related to the hypotheses of this study and widely considered potential drivers of vegetation productivity in Guizhou [35][36][37] . More details about these variables were provided below.…”
Section: Methodsmentioning
confidence: 99%
“…We used a total of seven predictor variables (Table 1) in order to explain the vegetation productivity. These variables were selected since they are related to the hypotheses of this study and widely considered potential drivers of vegetation productivity in Guizhou [35][36][37] . More details about these variables were provided below.…”
Section: Methodsmentioning
confidence: 99%
“…However, water balance is also related to evapotranspiration (Graham et al, 2019). Therefore, in analyzing climate effects on grassland vegetation, the drought index containing precipitation and evapotranspiration has an obvious advantage relative to precipitation (Zhou et al, 2019). The commonly used drought indicators are the SPI (Mckee et al, 1993), Palmer drought severity index (PDSI; Palmer, 1965), and SPEI (Vicente-Serrano et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…and vegetation types (broad-leaved forests, coniferous forests, etc.) [19,[28][29][30][31]. Regarding heat, a study by Ciais et al [32] showed that insufficient precipitation and an extreme increase in summer heat caused a decrease in vegetation productivity in Eastern and Western Europe in 2003.…”
Section: Introductionmentioning
confidence: 99%